Hubungan Antara Knowledge About Environmental Issues dan Environmental Sensitivity dengan Responsible Environmental Behavior Peserta Didik SMA Negeri d - Safitri Indah Lestari (Universitas Negeri Jakarta, 2022)
Environmental issues has increased continously over the last few years. The environmental issues are mostly brought about by human behavior in term of how they interact with the environment. The things that contribute to a person's behavior towards the environment are knowledge of environmental issues and environmental sensitivity. This study aims to determine the relationship between knowledge about environmental issues and environmental sensitivity with responsible environmental behavior that student have. The research was conducted at SMA Negeri 59 Jakarta on the 1st semester, in November, of 2022/2023 school year, involving as many as 70 student samples. The method used is a descriptive method with a correlational study approach using simple correlation regression and multiple analysis. The results of the study revealed that there was a positive and significant relationship between the knowledge about environmental issues with responsible environmental behavior; there was a positive and significant relationship between the environmental sensitivity with responsible environmental behavior; and there was a positive and significant relationship between knowledge about environmental issues and environmental sensitivity together with responsible environmental behavior. Therefore, in improving the responsible environmental behavior of students to be more positive, need to consider factors knowledge about environmental issues and environmental sensitivity of student that contribute significantly.